2017
DOI: 10.1039/c7sc00129k
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional crystal engineering using halogen and hydrogen bonds: towards structural landscapes

Abstract: We apply the concepts of supramolecular synthons and structural landscapes to 2D crystallization at the solution–solid interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 55 publications
1
49
0
Order By: Relevance
“…Two‐component halogen‐bonded networks (Figure d, e) were formed akin to those displayed in Figure b, c. The honeycomb network obtained using 10 as the halogen bond donor was found to contain the halogen bond acceptor as a guest molecule. The formation of an auto host‐guest system in this case indicated that strength of halogen bonds in this specific case is not enough to sustain the open network and that the molecular guests are needed to stabilize the supramolecular assembly …”
Section: Halogen‐halogen Interactions and Halogen‐bonding In Self‐assmentioning
confidence: 98%
“…Two‐component halogen‐bonded networks (Figure d, e) were formed akin to those displayed in Figure b, c. The honeycomb network obtained using 10 as the halogen bond donor was found to contain the halogen bond acceptor as a guest molecule. The formation of an auto host‐guest system in this case indicated that strength of halogen bonds in this specific case is not enough to sustain the open network and that the molecular guests are needed to stabilize the supramolecular assembly …”
Section: Halogen‐halogen Interactions and Halogen‐bonding In Self‐assmentioning
confidence: 98%
“…Recognition interactions between functional groups on different tectons then form supramolecular synthons 9 linking the tectons together and driving self-assembly. Coordination bonds, [10][11] halogen bonds, [12][13] van der Waals interactions, [14][15] and even dynamic covalent bond formation 15 have all been employed as recognition interactions in the growth of complex 2D molecular networks. Hydrogen bonds in particular have been widely used as stabilizing interactions for 2D self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonds in particular have been widely used as stabilizing interactions for 2D self-assembly. 1,[5][6]12 A key example of the use of hydrogen bonds as molecular recognition interactions in 2D self-assembly is the triple hydrogen bond interaction formed between perylenetetracarboxylic diimide (PTCDI) and melamine. [17][18][19] The archetypal set of supramolecular synthons based on hydrogen bonds are those formed between the nucleobases of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Halogen-bonded (XB) molecular nanostructures 1,[7][8][9] are considerably less common in on-surface 2D systems but are increasingly being studied and seen as an important addition to the 'toolbox' of supramolecular assembly. Typically, iodine [10][11][12][13][14] and bromine atoms [15][16][17][18][19] are used as halogen bond donors due to their strong polarisability, but examples of chlorine 20 and fluorine 21,22 based assemblies have also been reported. Halogen bonds can also involve halogen atoms acting simultaneously as both donor and acceptor 11,16,17,23,24 , with the positive electrostatic potential of the sigma hole oriented towards the central 'belt' of negative electrostatic potential found on an adjacent halogen atom.…”
mentioning
confidence: 99%